Temporal Variation of Boron in Bnynk Menderes River, Turkey - Dagdelen, Necdet; Yesilirmak, Ercan; Akcay, Selin; Koc, Cengiz (Asian Journal of Chemistry, 2010)
Boron is needed by plants in relatively small amounts. On the other hand, excessive amounts of boron would result in toxicity problems depending on the nature of plants, since some plants are sensitive to boron and some others are not. In some agricultural areas as in Büyük Menderes River basin, ground and surface water which is used for agricultural irrigation would contain appreciable amounts of boron due to geothermal fields. In this study, because of specific importance of boron for agricultural irrigation in Büyük Menderes river basin, temporal variation of boron concentrations observed at 9 water quality monitoring stations along Büyük Menderes River were evaluated using nonparametric Seasonal Kendall tets. Slopes of trends were obtained by using Seasonal Kendall Slope Estimator. The results were discussed on station basis.